pub theorem recS (z: nat) (S: set) (n: nat): $ rec z S (suc n) = S @ rec z S n $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
m = n -> suc m = suc n |
||
2 |
m = n -> rec z S (suc m) = rec z S (suc n) |
||
3 |
m = n -> rec z S m = rec z S n |
||
4 |
m = n -> S @ rec z S m = S @ rec z S n |
||
5 |
m = n -> (rec z S (suc m) = S @ rec z S m <-> rec z S (suc n) = S @ rec z S n) |
||
6 |
m = k -> suc m = suc k |
||
7 |
m = k -> rec z S (suc m) = rec z S (suc k) |
||
8 |
m = k -> rec z S m = rec z S k |
||
9 |
m = k -> S @ rec z S m = S @ rec z S k |
||
10 |
m = k -> (rec z S (suc m) = S @ rec z S m <-> rec z S (suc k) = S @ rec z S k) |
||
12 |
finite {x | x <= suc k} |
||
13 |
E. a A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) |
||
14 |
rec z S 0 = z |
||
15 |
0 <= suc k |
||
16 |
x = 0 -> (x <= suc k <-> 0 <= suc k) |
||
17 |
x = 0 -> pset a @ x = pset a @ 0 |
||
18 |
~x = suc k -> if (x = suc k) (S @ rec z S k) (rec z S x) = rec z S x |
||
20 |
x = suc k -> x != 0 |
||
21 |
conv ne |
x = suc k -> ~x = 0 |
|
22 |
con2* |
x = 0 -> ~x = suc k |
|
23 |
x = 0 -> if (x = suc k) (S @ rec z S k) (rec z S x) = rec z S x |
||
24 |
x = 0 -> rec z S x = rec z S 0 |
||
25 |
x = 0 -> if (x = suc k) (S @ rec z S k) (rec z S x) = rec z S 0 |
||
26 |
x = 0 -> (pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> pset a @ 0 = rec z S 0) |
||
27 |
x = 0 -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> 0 <= suc k -> pset a @ 0 = rec z S 0) |
||
28 |
A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> 0 <= suc k -> pset a @ 0 = rec z S 0 |
||
29 |
A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> pset a @ 0 = rec z S 0 |
||
30 |
A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> pset a @ 0 = z |
||
31 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> pset a @ 0 = z |
||
32 |
suc k <= suc k |
||
33 |
x = suc k -> (x <= suc k <-> suc k <= suc k) |
||
34 |
x = suc k -> pset a @ x = pset a @ suc k |
||
35 |
x = suc k -> if (x = suc k) (S @ rec z S k) (rec z S x) = S @ rec z S k |
||
36 |
x = suc k -> (pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> pset a @ suc k = S @ rec z S k) |
||
37 |
x = suc k -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> suc k <= suc k -> pset a @ suc k = S @ rec z S k) |
||
38 |
A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> suc k <= suc k -> pset a @ suc k = S @ rec z S k |
||
39 |
A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> pset a @ suc k = S @ rec z S k |
||
40 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> pset a @ suc k = S @ rec z S k |
||
41 |
y <= k <-> y < suc k |
||
42 |
y <= k <-> suc y <= suc k |
||
43 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> y <= k |
||
44 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> suc y <= suc k |
||
45 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) |
||
46 |
x = suc y -> (x <= suc k <-> suc y <= suc k) |
||
47 |
x = suc y -> pset a @ x = pset a @ suc y |
||
48 |
suc y = suc k <-> y = k |
||
49 |
x = suc y -> (x = suc k <-> suc y = suc k) |
||
50 |
x = suc y -> (x = suc k <-> y = k) |
||
51 |
x = suc y -> S @ rec z S k = S @ rec z S k |
||
52 |
x = suc y -> rec z S x = rec z S (suc y) |
||
53 |
x = suc y -> if (x = suc k) (S @ rec z S k) (rec z S x) = if (y = k) (S @ rec z S k) (rec z S (suc y)) |
||
54 |
x = suc y -> (pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> pset a @ suc y = if (y = k) (S @ rec z S k) (rec z S (suc y))) |
||
55 |
x = suc y -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> suc y <= suc k -> pset a @ suc y = if (y = k) (S @ rec z S k) (rec z S (suc y))) |
||
56 |
A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> suc y <= suc k -> pset a @ suc y = if (y = k) (S @ rec z S k) (rec z S (suc y)) |
||
57 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> suc y <= suc k -> pset a @ suc y = if (y = k) (S @ rec z S k) (rec z S (suc y)) |
||
58 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> pset a @ suc y = if (y = k) (S @ rec z S k) (rec z S (suc y)) |
||
59 |
y = k -> if (y = k) (S @ rec z S k) (rec z S (suc y)) = S @ rec z S k |
||
60 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ y = k -> if (y = k) (S @ rec z S k) (rec z S (suc y)) = S @ rec z S k |
||
61 |
pset a @ y = rec z S y -> rec z S y = pset a @ y |
||
62 |
x <= suc k -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) |
||
63 |
x = y -> (x <= suc k <-> y <= suc k) |
||
64 |
y <= k /\ x = y -> (x <= suc k <-> y <= suc k) |
||
65 |
y <= k /\ x = y -> y <= k |
||
66 |
k <= suc k |
||
67 |
y <= k /\ x = y -> k <= suc k |
||
68 |
y <= k /\ x = y -> y <= suc k |
||
69 |
y <= k /\ x = y -> x <= suc k |
||
70 |
y <= k /\ x = y -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) |
||
71 |
x = y -> pset a @ x = pset a @ y |
||
72 |
y <= k /\ x = y -> pset a @ x = pset a @ y |
||
73 |
x < suc k -> x != suc k |
||
74 |
conv ne |
x < suc k -> ~x = suc k |
|
75 |
x <= k <-> x < suc k |
||
76 |
x = y -> (x <= k <-> y <= k) |
||
77 |
y <= k -> y <= k |
||
78 |
y <= k -> x = y -> x <= k |
||
79 |
y <= k /\ x = y -> x <= k |
||
80 |
y <= k /\ x = y -> x < suc k |
||
81 |
y <= k /\ x = y -> ~x = suc k |
||
82 |
y <= k /\ x = y -> if (x = suc k) (S @ rec z S k) (rec z S x) = rec z S x |
||
83 |
x = y -> rec z S x = rec z S y |
||
84 |
y <= k /\ x = y -> rec z S x = rec z S y |
||
85 |
y <= k /\ x = y -> if (x = suc k) (S @ rec z S k) (rec z S x) = rec z S y |
||
86 |
y <= k /\ x = y -> (pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> pset a @ y = rec z S y) |
||
87 |
y <= k /\ x = y -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x) <-> pset a @ y = rec z S y) |
||
88 |
y <= k /\ x = y -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> pset a @ y = rec z S y |
||
89 |
y <= k /\ x = y -> (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> rec z S y = pset a @ y |
||
90 |
y <= k -> A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> rec z S y = pset a @ y |
||
91 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> rec z S y = pset a @ y |
||
92 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> rec z S y = pset a @ y |
||
93 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ y = k -> rec z S y = pset a @ y |
||
94 |
y = k -> rec z S y = rec z S k |
||
95 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ y = k -> rec z S y = rec z S k |
||
96 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ y = k -> pset a @ y = rec z S k |
||
97 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ y = k -> S @ (pset a @ y) = S @ rec z S k |
||
98 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ y = k -> if (y = k) (S @ rec z S k) (rec z S (suc y)) = S @ (pset a @ y) |
||
99 |
~y = k -> if (y = k) (S @ rec z S k) (rec z S (suc y)) = rec z S (suc y) |
||
100 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> if (y = k) (S @ rec z S k) (rec z S (suc y)) = rec z S (suc y) |
||
101 |
y < k \/ y = k -> y = k \/ y < k |
||
102 |
conv or |
y < k \/ y = k -> ~y = k -> y < k |
|
103 |
y <= k <-> y < k \/ y = k |
||
104 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> y < k \/ y = k |
||
105 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> ~y = k -> y < k |
||
106 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> y < k |
||
107 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> A. m (m < k -> rec z S (suc m) = S @ rec z S m) |
||
108 |
m = y -> (m < k <-> y < k) |
||
109 |
m = y -> suc m = suc y |
||
110 |
m = y -> rec z S (suc m) = rec z S (suc y) |
||
111 |
m = y -> rec z S m = rec z S y |
||
112 |
m = y -> S @ rec z S m = S @ rec z S y |
||
113 |
m = y -> (rec z S (suc m) = S @ rec z S m <-> rec z S (suc y) = S @ rec z S y) |
||
114 |
m = y -> (m < k -> rec z S (suc m) = S @ rec z S m <-> y < k -> rec z S (suc y) = S @ rec z S y) |
||
115 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) -> y < k -> rec z S (suc y) = S @ rec z S y |
||
116 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> y < k -> rec z S (suc y) = S @ rec z S y |
||
117 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> rec z S (suc y) = S @ rec z S y |
||
118 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> rec z S y = pset a @ y |
||
119 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> S @ rec z S y = S @ (pset a @ y) |
||
120 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> rec z S (suc y) = S @ (pset a @ y) |
||
121 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k /\ ~y = k -> if (y = k) (S @ rec z S k) (rec z S (suc y)) = S @ (pset a @ y) |
||
122 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> if (y = k) (S @ rec z S k) (rec z S (suc y)) = S @ (pset a @ y) |
||
123 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) /\ y <= k -> pset a @ suc y = S @ (pset a @ y) |
||
124 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> y <= k -> pset a @ suc y = S @ (pset a @ y) |
||
125 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> y < suc k -> pset a @ suc y = S @ (pset a @ y) |
||
126 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> A. y (y < suc k -> pset a @ suc y = S @ (pset a @ y)) |
||
127 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) /\ A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> rec z S (suc k) = S @ rec z S k |
||
128 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) -> E. a A. x (x <= suc k -> pset a @ x = if (x = suc k) (S @ rec z S k) (rec z S x)) -> rec z S (suc k) = S @ rec z S k |
||
129 |
A. m (m < k -> rec z S (suc m) = S @ rec z S m) -> rec z S (suc k) = S @ rec z S k |
||
130 |
T. /\ A. m (m < k -> rec z S (suc m) = S @ rec z S m) -> rec z S (suc k) = S @ rec z S k |
||
131 |
T. -> rec z S (suc n) = S @ rec z S n |
||
132 |
rec z S (suc n) = S @ rec z S n |